KESIAPAN KEPEMIMPINAN IGD DALAM PEMENUHAN STANDAR IGD RUMAH SAKIT TIPE B DAN INDIKATOR MUTU IGD RSU PKU MUHAMMDIYAH BANTUL - Muhammad Firdaus; Susianti Miranda Boru Surbakti (Journal of Hospital Administration and Management, 2020)
In 2014 the E.R service of PKU Muhammadiyah Bantul Hospital should be suitable with the service standard of III level/ B type hospital. It, however , cannot be analyzed whether the E.R of PKU Muhammadiyah Bantul Hospital has started to adjust the hospital E.R standard that has been appointed based on Health Minister Decree of Republic of Indonesia No. 858/Menkes/SK/IX/2009 about the principal hospital E.R standard in the emergency service. To bring it into reality, strategies are needed in order that the adjustment of the E.R standard to B type hospital can run well. One of the ways is by measuring four dimensions of transformational leadership in the fulfillment process of the B type hospital E.R standard. Assessing the leadership readiness of Emergency Room in PKU Muhammadiyah Bantul Hospital in fulfilling the E.R standard of B type hospital, by assessing four dimensions of transformational leadership, i.e.: (1) idealized influence, (2) inspirational motivation, (3) intellectual stimulation, (4) individualized consideration. This research is a descriptive qualitative research with a case study. The data collection is carried out through observation and interview. The primary data is obtained from the answer results and observation from the research questions and the secondary data is obtained in form of the service standard of the emergency room in PKU Muhammadiyah Bantul Hospital type C, SOP, books and Director Decree. The research was held on June, 2011. The emergency room service standard of PKU Muhammadiyah Bantul Hospital type C, based on Indonesian Health Minister Decree has been fulfilled. To go to B type hospital, it needs 100% service type category, human resources category 66,7%, facility 60%, medical and non-medical facility 50%. Nine quality indicators of the emergency room in PKU Muhammadiyah Bantul Hospital has been fulfilled as a whole and the leadership readiness of the emergency room in PKU Muhammadiyah Bantul Hospital to B type has not been ready since the first year of the hospital strategic plan (renstra) was determined. The service standard of the emergency room of PKU Muhammadiyah Bantul Hospital type C based on Indonesian Health Minister has been fulfilled, to go to B type, there is still a gap, but it has been anticipated by the working program and the leadership readiness of the emergency room is not ready as a whole in the first year since the hospital strategic plan (renstra) was determined